Spontaneous Retroperitoneal Bleeding as a Complication of Unusual Renal Paraganglioma. (30th August 2022) - Sangey, Tawfeeq I.; Abdul Rusheke, Hamim; Sangey, Ansaar I.; Chaya, Nimishkumar; Ngaiza, Advera
Abstract : Spontaneous retroperitoneal bleeding is a rare occurrence that might have catastrophic implications. We present a 58-year-old male with a 4-day history of progressively worsening left-sided flank pain due to retroperitoneal hemorrhage from a nonfunctional renal paraganglioma. Abdominal contrast CT scan was helpful in locating the tumor, estimating tumor size and extent of bleeding, visualizing the interaction between the tumor and the surroundings, and ruling out any potential metastasis; however, it lacked specificity in identifying the origin of the mass, needing histologic investigation for a conclusive diagnosis. MRI was not available at our center. We report a rare case of spontaneous retroperitoneal bleeding as a complication of an unusual nonfunctional renal paraganglioma, which was initially misdiagnosed as renal cell carcinoma but later confirmed by postoperative histopathology.